Basic Soft Skills for Law Mediatorsdevelopment Couching With “You Are My Figure” Game - Pamuji, Wirawan; Dahlia Nopelina Siallagan; Rini T Simangunsong (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Model of mediation attitudes at court is not merely alike in skills of knowledge at all, the way of implementing court activity for Justice way does not support itself not only with superiority of adequate skills for completing jobs, but also supported with attitudes. The Research applies Descriptive Qualitative Methods in developing Domain of Affective Taxonomy in developing mediators’ soft skill attitudes in performing excellence at court as mediators. The application of this couching is about to implement about staff manner adjustment in facing interview before accepting a job